Identification of coagulase‐negative staphylococci in daily disposable contact lens wearers. (1st September 2014) - Hall, B.; McCanna, D.; Jones, L.
Abstract: This study aimed to identify and quantify the number of contaminating organisms on daily disposable (DD) soft contact lenses, which may be responsible for mild cases of keratitis that occur with this lens wear modality. Ten participants wore DD lenses, and 10 participants wore planned replacement (PR) lenses. Lenses were collected aseptically and analysed for microbial contamination. Colony‐forming units (CFU) were recorded, and representative colonies were used for identification using the API identification system. The DD lenses evaluated in this study were contaminated with coagulase‐negative staphylococcus (CNS), ranging from 1 to 653 CFU. PR lenses showed more diversity in the types of contaminating micro‐organisms and consisted of CNS, Gram‐negative bacteria ( Pseudomonas ), a yeast ( Candida ) and a mould ( Aspergillus ), ranging from 1 to 230 CFU. CNS was the only type of micro‐organism found on DD contact lenses and therefore may be the cause of any form of keratitis observed in DD lens wearers. Significance and Impact of the Study: This is the first study to determine the frequency and identify the contaminating organisms found on daily disposable (DD) soft contact lenses. The contaminating organisms identified on DD contact lenses were solely coagulase‐negative staphylococcus (CNS), suggesting that CNS may be the causative organism associated with infectious keratitis that occurs with DD contact lens wear.